2019
DOI: 10.1002/cam4.2644
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of a nomogram for melanomas with brain metastases at initial diagnosis

Abstract: Background Estimation of incidence and prognosis of melanomas with brain metastases (MBM) at initial diagnosis based on a large cohort is lacking in current research. This study aims to construct an effective prognostic nomogram for newly diagnosed MBM. Materials and Methods Patients diagnosed with melanomas from Surveillance, Epidemiology, and End Results program between 2010 and 2014 were enrolled in our study. Risk factors predicting brain metastases (BM) were identified using logistic regression analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
3
7
0
Order By: Relevance
“…These findings show that patients with HNM require close follow-up. Ulceration, lymph node stage and metastasis have been identified as significant independent factors of cutaneous melanoma in previous studies and were also identified in our study [26,28].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These findings show that patients with HNM require close follow-up. Ulceration, lymph node stage and metastasis have been identified as significant independent factors of cutaneous melanoma in previous studies and were also identified in our study [26,28].…”
Section: Discussionsupporting
confidence: 83%
“…The Surveillance, Epidemiology, and End Results (SEER) database provides information on cancer incidence, treatment and survival from 18 population-based cancer registries, covering 28% of the US population [23]. Many studies have utilized the high-quality database to analyze melanoma characteristics, risks and prognoses [24][25][26]. Lachiewicz et al collected SEER data from 1992 to 2003 to examine survival differences between patients with scalp or neck melanoma and those with melanoma of other sites [27].…”
Section: Introductionmentioning
confidence: 99%
“…Ulceration, lymph node stage and metastasis have been identi ed as signi cant independent factors of cutaneous melanoma in previous studies and were also identi ed in our study [26,27]. Notably, when presenting distant metastasis, compared to HNM patients, BM patients had worse 5-year CSS and OS rates.…”
Section: Discussionsupporting
confidence: 74%
“…Kevin et al [14] performed a comparison of 4561 pediatric patients with HNM or BM, but they did not study prognostic factors. Previous studies have identi ed signi cant independent prognostic factors of melanoma, and some nomograms were developed for predicting the OS or CSS of nonmetastatic melanoma patients, melanoma patients with brain metastases or nodular melanoma patients [6,[24][25][26][27]. To date, a speci c nomogram for HNM or BM has not been developed.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 To date, nomogram is widely used to help physician accurately and timely estimate the prognosis of patients. 15,17 Previous several studies have reported that primary clinical features were correlated with prognosis of patients with CMMs, 15,18,19 but few studies constructed a nomogram, based on those common clinical features, to predict the survival rate of patients with NMMM. 19 Therefore, our purpose of the present study was to identify clinicopathological factors associated with prognosis basing on the data from SEER database.…”
Section: Introductionmentioning
confidence: 99%